Moving through cancer : an exercise and strength-training program for the fight of your life - Schmitz, Kathryn; Miller, Gabriel (Food writer) (Chronicle Prism, 2021)
"Dr. Kathryn Schmitz overturned years of entrenched dogma and conventional wisdom that told breast cancer survivors to avoid upper body exercise with the publication of two ground-breaking scientific papers in the most prestigious medical journals in the world, the New England Journal of Medicine and the Journal of the American Medical Association. In the ensuing decade, Dr. Schmitz has made it her personal mission to use exercise for cancer prevention and recovery, for all cancers, in the same way it has been used for heart disease-only better. Her experiences with the thousands of cancer patients she has treated during two decades researching the physical and mental benefits of exercise, have led to the simple program at the heart of this book: MOVE, LIFT, EAT, and SLEEP. Together with creating a daily log to track how patients are feeling, these five steps have the potential to transform the cancer journey. And science has shown that taking these steps can also improve one's chances of beating cancer and preventing cancer from coming back"--